Clinical efficacy of an ultrasound-guided bilateral rectus sheath block for umbilical hernia repair in calves: A prospective randomized trial - Micieli, Fabiana; Guccione, Jacopo; Della Valle, Giovanni; Alterisio, Maria Chiara; Ciaramella, Paolo; Vesce, Giancarlo; Chiavaccini, Ludovica (Frontiers in Pain Research, 2023)
Surgical umbilical hernia repair is a frequent procedure in newborn calves, requiring mandatory pain management. This study aimed to develop an ultrasound-guided rectus sheath block (RSB) and to evaluate its clinical efficacy in calves undergoing umbilical herniorrhaphy under general field anesthesia. Gross and ultrasound anatomy of the ventral abdomen and the diffusion of a new methylene blue solution after injection within the rectus sheath were described in seven fresh calf cadavers. Then, fourteen calves undergoing elective herniorrhaphy were randomly assigned to receive either bilateral ultrasound-guided RSB with 0.3 mL/kg of bupivacaine 0.25% and 0.15 µg/kg of dexmedetomidine or 0.3 mL/kg of 0.9% NaCl (control). Intraoperative data included cardiopulmonary variables and anesthetic requirements. Postoperative data included pain scores, sedation scores and peri-incisional mechanical threshold assessed by force algometry at specific time points after anesthetic recovery. Treatments were compared using Wilcoxon rank-sum, Student’s t-test, and Cox proportional hazard model as appropriate. Mixed effect linear models on rank, with random effect calf; fixed effects time, treatment, and their interaction were used to compare pain scores and mechanical thresholds over time. Significance was set at p = 0.05. Calves receiving RSB recorded lower pain scores between 45 - 120 minutes (p < 0.05) and at 240 min after recovery (p = 0.02). And they recorded higher mechanical thresholds between 45 and 120 min after surgery (p < 0.05). Ultrasound-guided RSB provided effective perioperative analgesia in calves undergoing herniorrhaphy under field conditions.